2018
DOI: 10.1021/acs.iecr.8b00913
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Facile Synthesis of Graphene Quantum Dots from Rice Husks for Fe3+ Sensing

Abstract: In this work, graphene quantum dots (GQDs) with an average size of 3.9 nm were synthesized using rice husk biomass as the raw material via a facile one-step one-pot hydrothermal method. The size and morphology of the rice husk-derived GQDs were characterized by transmission electron microscopy and atomic force microscopy. The GQDs exhibit bright blue photoluminescence under 365 nm ultraviolet irradiation and can be well dispersed in water. The GQDs reach the strongest photoluminescence excitation intensity at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 58 publications
1
56
1
Order By: Relevance
“…They also wrote about the Fe-GQDs complexes that promote charge transfer between them. Based on the plotted graph, a linear relation was observed between PL response and Fe 3+ concentration raised to 10 mM, and the calculated detection limit equaled 5.8 nM [41].…”
Section: Incorporation Of Graphene Quantum Dots With Optical Sensomentioning
confidence: 99%
“…They also wrote about the Fe-GQDs complexes that promote charge transfer between them. Based on the plotted graph, a linear relation was observed between PL response and Fe 3+ concentration raised to 10 mM, and the calculated detection limit equaled 5.8 nM [41].…”
Section: Incorporation Of Graphene Quantum Dots With Optical Sensomentioning
confidence: 99%
“…The properties of CDs such as highly fluorescent, environment-friendly and facile synthesis make them suitable materials for ion detection. Based on the fluorescence quenching or enhancement caused by the interactions with ions, CDs can be applied in the detection of multiple ions, such as Fe 3+ , Pb 2+ Hg 2+ , Cr 6+ , Cr 3+ , Be 2+ , ClO − , ONOO − and I − 1826 . However, detection of ferricyanide ([Fe(CN) 6 ] 3− ) by fluorescent probe based on CDs has not been reported previously.…”
Section: Introductionmentioning
confidence: 99%
“…Since the phenolic hydroxyl groups in LBE molecule could form complexes with Fe 3+ ions as an electron donor, which was beneficial to facilitate charge transfer (Guo et al, 2015 ; Shen et al, 2017 ). The recombination of excitons was inhibited and then a significant fluorescence quenching occurred (Zhang Y. L. et al, 2013 ; Wang et al, 2018 ). Figure 7B and Figure S10 showed the relative fluorescence response of LBE(I 0 /I) according to the concentration of Fe 3+ , where I 0 and I are the fluorescence intensities of LBE in the absence and presence of Fe 3+ ions, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This value is well below the maximum allowable level of Fe 3+ in drinking water set by the World Health Organization (5.36 μM), Moreover, the method of detecting Fe 3+ based on carbon dots in this article was comparable or even better than that in other previous reports (Shen et al, 2017 ; Chen et al, 2019 ; Arumugham et al, 2020 ). The results indicated that LBE owned a good application prospect in the detection of trace Fe 3+ due to the low LOD of Fe 3+ (Wang et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%